NMR artifacts caused by decoupling of multiple-spin coherences: improved SLAP experiment - Blechta, Vratislav; Schraml, Jan (Magnetic resonance in chemistry, 2015)
Contrary to common expectations, multiple-spin coherences containing products of proton and heteronucleus operators (e.g. Hu Cx , u = x, y, z) can produce not only sidebands but also noticeable centerband NMR signals of the heteronucleus during acquisition under 1H broadband decoupling. Such centerband signals of low abundant heteronuclei can be sources of relatively strong unexpected artifacts in NMR experiments that aim to detect very weak signals from much less-abundant isotopomers, e.g. 13C-13C ones. These findings lead to a new design of Sign Labeled Polarization Transfer (SLAP) pulse sequence (MSS-SLAP) with improved suppression of centerband peaks that are because of singly, e.g. 13C, labeled molecules (parent peaks). The MSS-SLAP experiment and its MSS-BIRD-SLAP variant are compared with a few older SLAP versions.
Keywords: composite decoupling; signs of coupling constants; double-quantum filter; SLAP; BIRD; 13C; NMR; 13C-13C coupling constants